Rebound Thymic Hyperplasia after Chemotherapy in Children with Lymphoma - Chih-Ho Chen; Chih-Chen Hsiao; Yu-Chieh Chen; Sheung-Fat Ko; Shu-Hua Huang; Shun-Chen Huang; Kai-Sheng Hsieh; Jiunn-Ming Sheen (Pediatrics and Neonatology)
Development of mediastinal masses after completion of chemotherapy in pediatric patients with malignant lymphoma is worrisome and challenging to clinicians. Methods: We performed a retrospective review of 67 patients with lymphoma treated at our hospital from January 1, 2001 to June 1, 2013. Patients who received at least two chest computed tomography (CT) examinations after complete remission (CR) was achieved were further analyzed. Gallium-67 scans and positron emission tomography (PET) were recorded and compared between these patients. Results: Sixty-two of 67 patients reached CR, of whom 31 (22 male, 9 female) were patients that received at least two chest CT examinations after CR. Rebound thymic hyperplasia (RTH) was diagnosed in 21/31 patients (67.7%), including 14/23 (60.9%) and seven out of eight (87.5%) with non-Hodgkin's lymphoma and Hodgkin's lymphoma, respectively. Ages ranged from 3 years to 18 years (median 10 years). Increased radioactivity uptake of the anterior mediastinum in gallium scans was found in nine out of 20 patients (45%) with thymic rebound. PET was performed in six out of 21 patients. Increased fluorodeoxyglucose (FDG)-avid uptake in the anterior mediastinum was observed in four of six patients (66.7%) by PET. One patient received thymectomy. No patients with RTH had lymphoma relapse within the median follow-up period (5 years). Relapse was statistically significantly different (p = 0.001) between patients with and without RTH. Conclusion: RTH developed in 67.7% of pediatric patients with lymphoma in CR after chemotherapy. The association of RTH development and lowered relapse rates has yet to be determined. Awareness of this phenomenon is important in the prevention of unnecessary surgical intervention or chemotherapy.